The pipfruit export season at the Port of Napier container terminal : an exploratory case study : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Logistics and Supply Chain Management at Massey University, Palmerston North - Mudzamba, Karl Mberikwazvo Tichatonga (Massey University, 2010)
This is an exploratory study seeking to gain a better understanding of seasonality at the Port of Napier container terminal. It seeks to explore the motives behind the actions of the pipfruit exporters, and analyse the impact seasonal reefer (refrigerated containers) volumes have on terminal operations. The case study method is employed because it reflects the interpretive assumptions adopted for the study, and has the tools to analyse the qualitative and quantitative data collected. The study revealed the exporters source most of their fruit from their own and leased orchards. The guaranteed volumes justify the investments made in fruit handling facilities. The balance of their fruit comes from contract growers where the exporters seek to establish long term relationships to minimise supply uncertainty. The exporters look to using their own fruit handling facilities, before passing any fruit to third parties, because of the greater flexibility afforded by prioritising shipments in their own facilities. The exporters have invested in information systems that have automated most of the previously manual processes, and assist with managing the complexity of compliance, improving visibility in their operations, and satisfying the traceability requirements of their customers. The exporters have retail programs in place with customers in their traditional markets (US and Europe) that enable them to manage their work load for the entire season. The exporters have increasingly directed marketing efforts to the fixed price markets in mostly Asia, the Middle East and Russia, because the upfront payments, shorter transit times and fixed prices, reduce the risk of serving the markets. The fixed price sales are very much on short notice and present unique challenges on logistic systems, as the emphasis is on expediting shipments to get the best prices. The success of exclusive varieties and licensed orchards give the exporters much hope, particularly with the latter, as they are able to maintain fresh supplies all year round. The exporters select shipping lines on the basis of transit times and port calls but are in reality, at the mercy of the powerful shipping lines They have to base their marketing plans on the schedules of the lines. Chartering offers a way around the rigid schedules of the shipping lines, though only one exporter currently exercises this option. The impact of the pipfruit export season in the terminal is evident on its impact on several aspects of terminal operations. Container vessel calls increase, as shipping lines deploy ‘extra loaders’ to complement their regular services to deal with the added cargo volumes. Vessel exchange times lengthen to reflect the increase in containers exchanged. Reefer capacity utilisation rises well above the average, though reefer dwell times decrease to reflect the pressure exporters work under during the season that almost reduces them to packing reefers just-in-time for vessels. The number of rehandles rises to mimic the added container volumes as the terminal employs strategies to cope with the scarcity of reefer space.
Keywords: Exploratory case study; Port of Napier; Logistics and Supply Chain Management; New Zealand pipfruit industry; Seasonality; Container terminals; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management